Expression of Proinflammatory and Regulatory Cytokines via NF-κB and MAPK-Dependent and IFN Regulatory Factor-3-Independent Mechanisms in Human Primary Monocytes Infected by Mycobacterium tuberculosis - Elena Giacomini; Maria Elena Remoli; Marta Scandurra; Valérie Gafa; Manuela Pardini; Lanfranco Fattorini; Eliana M. Coccia (Clinical and Developmental Immunology)
Knowledge of the molecular events regulating the innate response to Mycobacterium tuberculosis (Mtb) is critical for understanding immunological pathogenesis and protection from tuberculosis. To this aim, the regulation and the expression of regulatory and proinflammatory cytokines were investigated in human primary monocytes upon Mtb infection. We found that Mtb-infected monocytes preferentially express a proinflammatory cytokine profile, including IL-6, TNF-α, and IL-1β. Conversely, among the regulatory cytokines, Mtb elicited IL-10 and IL-23 release while no expression of IL-12p70, IL-27, and IFN-β was observed. The analysis of the signalling pathways leading to this selective cytokine expression showed that in monocytes Mtb activates MAPK and NF-κB but is unable to stimulate IRF-3 phosphorylation, a transcription factor required for IL-12p35 and IFN-β gene expression. Thus, by inducing a specific cytokine profile, Mtb can influence the immunoregulatory properties of monocytes, which represent important target of novel vaccinal strategies against Mtb infection.